Source localization comparison and combination of OPM-MEG and fMRI to detect sensorimotor cortex responses - An, Nan; Gao, Zhenfeng; Li, Wen; Cao, Fuzhi; Wang, Wenli; Xu, Weinan; Wang, Chunhui; Xiang, Min; Gao, Yang; Wang, Dawei; Yu, Dexin; Ning, Xiaolin (Computer methods and programs in biomedicine, 2024)
The exploration of various neuroimaging techniques have become focal points within the field of neuroscience research. Magnetoencephalography based on optically pumped magnetometers (OPM-MEG) has shown significant potential to be the next generation of functional neuroimaging with the advantages of high signal intensity and flexible sensor arrangement. In this study, we constructed a 31-channel OPM-MEG system and performed a preliminary comparison of the temporal and spatial relationship between magnetic responses measured by OPM-MEG and blood-oxygen-level-dependent signals detected by functional magnetic resonance imaging (fMRI) during a grasping task. For OPM-MEG, the β-band (15–30 Hz) oscillatory activities can be reliably detected across multiple subjects and multiple session runs. To effectively localize the inhibitory oscillatory activities, a source power-spectrum ratio-based imaging method was proposed. This approach was compared with conventional source imaging methods, such as minimum norm-type and beamformer methods, and was applied in OPM-MEG source analysis. Subsequently, the spatial and temporal responses at the source-level between OPM-MEG and fMRI were analyzed. The effectiveness of the proposed method was confirmed through simulations compared to benchmark methods. Our demonstration revealed an average spatial separation of 10.57 ± 4.41 mm between the localization results of OPM-MEG and fMRI across four subjects. Furthermore, the fMRI-constrained OPM-MEG localization results indicated a more focused imaging extent. Taken together, the performance exhibited by OPM-MEG positions it as a potential instrument for functional surgery assessment. •The brain responses measured by OPM-MEG and fMRI were investigated and compared.•A source power-spectrum ratio-based imaging method was proposed and applied.•Simulations and experiments validated the effectiveness of the proposed method.•Fidelities across multiple subjects and runs demonstrated the performance of OPM-MEG.